The effect of support type and support visibility on performance in a football aiming task: Evidence from two experimental studies - Moll, T.; Rees, T.; Freeman, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Prior to matches, football players often receive final words of encouragement and/or advice from coaches or fellow players. Though this is presumed to help, the effects of provided support are frequently mixed (Uchino, 2009). Providing support might alleviate distress and enhance problem-solving but may also come across as pressuring and threaten a recipient`s sense of efficacy and autonomy (Bolger & Amarel, 2007). Recent research suggests that both the type of support (e.g., esteem or informational) and the way support is delivered (visibly or invisibly) may influence the effectiveness of support (Bolger & Amarel, 2007). We explore the effect of support type and support visibility in a performance setting. Method: In two experiments (study one, n = 68, study two, n = 84), we examined the effects of support type and support visibility on a football aiming task. Type of support was manipulated by changing the content (esteem or informational support) of the supportive message. Visibility was manipulated by addressing the support directly (visible) to the participant or indirectly by addressing the support to one of the experimenters (invisible). Experienced football players were randomly assigned to one of four support conditions: informational-visible, informational-invisible, esteem-visible, and esteem-invisible support. The players were told that an expert in penalty taking would be watching the task. In reality, this expert was a confederate scripted to provide one of the four support manipulations. Following the support manipulation, the players performed ten kicks towards a target. Performance was assessed as the average distance from the target. Results: Two-way ANOVAs revealed a significant main effect for type of support on kicking performance (Study 1, F(3,64) = 12.72, p < .01; Study 2, F(3,80) = 7.48, p < .01). There were no significant main effects for support visibility and no interaction effects (p > .05). Discussion: The results suggest that, regardless of support visibility, participants in the informational support conditions outperformed those in the esteem support conditions. That is, giving advice (in a visible or invisible manner) prior to a kicking task appears to be more effective than giving encouragement. It may be that in a sports environment athletes are used to receiving (and expect to receive) advice from coaches. Furthermore, the quality of the informational advice (`Focus on the target`) may have aided performance and not come across as pressuring or threatening; conversely, the esteem encouragement (`I`m sure you can do well`) may have led to pressure and poorer performance.